Genes, athlete status and training - An overview - Ahmetov, I. I.; Rogozkin, V. A. (Genetics and Sports, 2009)
Significant data confirming the influence of genes on human physical performance and elite athlete status have been accumulated in recent years. Research of gene variants that may explain differences in physical capabilities and training-induced effects between subjects is widely carried out. In this review, the findings of genetic studies investigating DNA polymorphisms and their association with elite athlete status and training responses are reported. A literature search revealed that at least 36 genetic markers (located within 20 autosomal genes, mitochondrial DNA and Y-chromosome) are linked to elite athlete status and 39 genetic markers (located within 19 genes and mitochondrial DNA) may explain, in part, an interindividual variability of physical performance characteristics in response to endurance/strength training. Although more replication studies are needed, the preliminary data suggest an opportunity to use some of these genetic markers in an individually tailored prescription of lifestyle/exercise for health and sports performance. (Autorreferat)